Book review: SIGNIFICANCE AND ROLE OF THE COMMUNIST PARTY OF CHINA IN GLOBAL POWER PROJECTION (International Journal of Contemporary Security Studies, 2024)
Chinese socialism and the modern world order (One hundred years since the founding of the Chinese Communist Party)Belgrade: Faculty of security studies